2008
DOI: 10.1002/sia.2956
|View full text |Cite
|
Sign up to set email alerts
|

The growth of thin NiO films on Ag(001) studied by scanning tunneling microscopy and spectroscopy

Abstract: We have used scanning tunneling microscopy and spectroscopy to study the growth of NiO films on Ag(001) at a coverage of 1.5 monolayers. The films have been obtained by reactive deposition of Ni in O-2 atmosphere. Particular attention has been paid to the development of the growth morphology of the deposit as a function of substrate and annealing temperature. For room temperature deposition, the Ag(001) surface is completely covered with the (2 x 1) NiO precursor structure with a thickness of one monolayer and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 24 publications
2
17
0
Order By: Relevance
“…Well-defined rectangular island shapes with polar island boundaries (i.e., rows of either Ni or O atoms) have been reported for annealing at 450 K in the absence of O 2 . 6,8 In contrast, Caffio et al have observed more roundish island shapes upon annealing at 500 K in vacuum and have ascribed the occurrence of the geometric island shapes to oxygen-rich annealing conditions. 7 In either case, however, the stoichiometry of the film appears to remain the same.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Well-defined rectangular island shapes with polar island boundaries (i.e., rows of either Ni or O atoms) have been reported for annealing at 450 K in the absence of O 2 . 6,8 In contrast, Caffio et al have observed more roundish island shapes upon annealing at 500 K in vacuum and have ascribed the occurrence of the geometric island shapes to oxygen-rich annealing conditions. 7 In either case, however, the stoichiometry of the film appears to remain the same.…”
Section: Introductionmentioning
confidence: 85%
“…[6][7][8] For submonolayer coverages, a NiO p(2 × 1) precursor phase forms upon deposition. The (2 × 1) phase is of monoatomic thickness and gradually covers the surface upon increasing the surface coverage.…”
Section: Introductionmentioning
confidence: 99%
“…For the deposition of metal films e-beam evaporators were available. The preparation of NiO films on a Ag(100) substrate is well documented [22][23][24][25][26][27]. The Ni evaporation was performed in an O 2 atmosphere of 10 −7 mbar.…”
Section: Methodsmentioning
confidence: 99%
“…For both cases, the oxides islands could be imaged as protrusions only at high V sample , which indi- cates the insulating nature of those islands. Großer et al 46 observed that the STM of 3-ML-thick NiO islands undergoes contrast reversal between two images obtained at V sample = 2.5 and 1 V. They also observed that 2-ML-thick NiO islands show contrast reversal between two V sample 's, although the contrast change is much less than those shown from the 3-ML-thick NiO islands.…”
Section: Morphological Changesmentioning
confidence: 84%
“…This indicates to the possibility of the some NiO layer͑s͒ embedded in Ag substrate, as also reported by many groups. 22,23,46 Therefore, we propose that the regions of 0.22 nm height in Fig. 3͑e͒ should be the NiO layers thicker than 2 ML.…”
Section: Morphological Changesmentioning
confidence: 99%